Circadian rhythm of heart rate and heart rate variability. Issue 2 (1st August 2000) - Massin, Martial M; Maeyns, Krystel; Withofs, Nadia; Ravet, Françoise; Gérard, Paul
Abstract : BACKGROUND: Measurements of heart rate variability (HRV) are increasingly used as markers of cardiac autonomic activity. AIM: To examine circadian variation in heart rate and HRV in children. SUBJECTS: A total of 57 healthy infants and children, aged 2 months to 15 years, underwent ambulatory 24 hour Holter recording. Monitoring was also performed on five teenagers with diabetes mellitus and subclinical vagal neuropathy in order to identify the origin of the circadian variation in HRV. METHODS: The following variables were determined hourly: mean RR interval, four time domain (SDNN, SDNNi, rMSSD, and pNN50) and four frequency domain indices (very low, low and high frequency indices, low to high frequency ratio). A chronobiological analysis was made by cosinor method for each variable. RESULTS: A significant circadian variation in heart rate and HRV was present from late infancy or early childhood, characterised by a rise during sleep, except for the low to high frequency ratio that increased during daytime. The appearance of these circadian rhythms was associated with sleep maturation. Time of peak variability did not depend on age. Circadian variation was normal in patients with diabetes mellitus. CONCLUSION: We have identified a circadian rhythm of heart rate and HRV in infants and children. Our data confirm a progressive maturation of the autonomic nervous system and support the hypothesis that the organisation of sleep, associated with sympathetic withdrawal, is responsible for these rhythms.